The Importance of Animal Biotechnology in Aquaculture Industry - Mohamad Badrul Hisyam, Mohamad Nor; Isaac Richard, Teo; Mierrah Natasha, Muhammad Nasir; Eva Arlynn Ayra, Mohd Faizul Faiz; Hung Hui, Chung (UNIMAS Publisher, 2025)
The fishing industry stands as one of Malaysia’s swiftly burgeoning sectors, constituting a significant portion of the national GDP (Figure 9.1). Over the past three decades, the industry had experienced rapid and dynamic growth, transitioning from traditional marine capture commodities to aquaculture commodities, which now make remarkable contributions (Kurniawan et al. 2021). This industry, which accounts for up to 0.2% of national GDP, has been successful in manufacturing and promoting high-value items to meet local demand and even export them internationally (FAO, 2016).